Editor in chief, DISCERN, International Journal of Design for Social Change, Sustainable Innovation and Entrepreneurship_CLONE - Souleles, Nicos (My University, 2026)
DISCERN is a scientific and cross-disciplinary research journal (ISSN digital: 2184-6995) with blind peer review, which publishes open access papers in the broad and multi-faceted area of design for social change. Through original conceptual, theoretical, and empirical research articles, it promotes and shares interdisciplinary and diverse knowledge related to the research and practice of design for social change, sustainable innovation, and entrepreneurship in an open, global and multidisciplinary perspective. https://www.designforsocialchange.org/journal/index.php/DISCERN-J/